THE INFLUENCE OF RISK PERCEPTION, EXPECTATION OF RETURN, AND BEHAVIORAL MOTIVATION ON THE INVESTMENT DECISIONS OF STUDENTS REGISTERED IN THE INVESTMENT GALLERY AT JAKARTA STATE UNIVERSITIES: PENGARUH PERSEPSI RISIKO, EKSPEKTASI RETURN, DAN BEHAVIORAL MOTIVATION TERHADAP KEPUTUSAN INVESTASI MAHASISWA YANG TERDAFTAR DI GALERI INVESTASI PADA PERGURUAN TINGGI NEGERI JAKARTA - Aditya Pratama; Achmad Fauzi; Unggul Purwohedi (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
This study aims to examine and analyze the effect of risk perceptions, return expectations, and behavioral motivation on investment decisions. The sampling technique used in this study is non-probability sampling through purposive sampling. This study uses primary data sources in the form of questionnaires with a population of 109 student investors, with a sample based on the criteria of 100 active student investors registered in the GIBEI FE UNJ, KSPM FEB UPNVJ, and CMSS PNJ investment gallery. The data analysis technique used in this study is descriptive statistical analysis, which is measured using SPSS v.25 software. The multiple linear regression analysis in this study includes a prerequisite test. The analysis shows that the data are normally distributed, linear, and there is no heteroscedasticity and multicollinearity. The feasibility test of the regression model, namely the F test, shows that the regression model is declared feasible. The coefficient of determination is the Adjusted R Square of 54.6% - which shows the magnitude of the influence of risk perception, return expectations, and behavioral motivation on investment decisions, while the rest is influenced by other variables which are not examined. The results of the t hypothesis test in this study show that: (a) Risk perception has a significant positive effect on investment decisions; (b) Expected Return has a significant positive effect on investment decisions; and (c) Behavioral Motivation has a significant positive effect on investment decisions